Asynchronous Android : harness the power of multi-core mobile processors to build responsive Android applications - Liles, Steve (Community experience distilled., 2013)
Concurrent Programming on Android is a step-by-step guide that builds a complete picture of the concurrency constructs available on the Android platform. This book is for Android developers who want to learn about the advanced concepts of Android programming. No prior knowledge of concurrency and asynchronous programming is required. This book is also targeted towards Java experts who are new to Android.